Intersectionality in Action: learnings, challenges & recommendations from IDRC-supported research in the global South - Dawson, Hannah J.; Lynch, Ingrid; Mhlana, Siviwe; Mokhema, Seipati (Southern Centre for Inequality Studies (SCIS), 2023)
The call for integrating intersectionality into development research and practice has surged in recent years. Advocates consider it a crucial perspective for understanding the interconnected forms in which oppression manifests and is experienced by marginalised groups of people. This approach is seen as valuable in crafting targeted, context-specific policy interventions to address diverse social problems. Despite its growing prominence and alignment with social justice agendas, confusion persists about what intersectionality entails. Ongoing debates centre on its origins, purpose and distinctiveness when compared to other conceptual tools and transformative methodologies. Existing intersectionality research often prioritises scholarship from the global North, particularly North America, which overlooks the diverse realities and perspectives of the global South. It is essential to highlight that intersectionality, as both a concept and a way of thinking, was present in various feminist traditions in the global South well before gaining prominence in the United States and academic discourse. Given the lack of a precise definition for intersectionality, scholars and practitioners increasingly emphasise the importance of investigating its application in specific research contexts and practical applications. The collaborative initiative "Promoting Intersectional Development Research," led by the Southern Centre for Inequality Studies (SCIS) at the University of the Witwatersrand and Canada's International Development Research Centre (IDRC), has provided an opportunity to interrogate the concept of intersectionality and critically evaluate its relevance for development research in and for the global South. The principal objective of this project is to “understand, inform and promote intersectional approaches to development research” across different programme initiatives of the IDRC. More specifically, the project aims to: 1. Document the diverse application of an intersectional approach in IDRC-supported research projects. 2. Synthesise the lessons on the benefits, limits and barriers of incorporating an intersectional approach into research, and identify opportunities and challenges for applying intersectionality to research dissemination, policy application and engagement. 3. Identify the needs for strengthening capacity among IDRC staff and partners to enhance understanding and facilitate practical learning about the application of an intersectional lens to development research. To achieve these objectives, SCIS partnered with eight organisations to examine their application of intersectionality in an IDRC-supported research project. The resulting case studies demonstrate intersectionality in action, exploring how diverse researchers and practitioners apply its concepts and principles. These studies reflect on the relevance and usefulness of employing an intersectional lens within diverse contexts and projects that employ a range of epistemological and methodological approaches. They offer insights into both the alignment and tensions associated with adopting an intersectional lens.
Synthesis report submitted by the Southern Centre for Inequality Studies (SCIS), University of the Witwatersrand.
Keywords: Intersectionality research; Global South; Collaboration; Canada; South Africa; SDG-5: Gender equality